Śāṅkhāyanaśrautasūtram = Sāṇkhāyana śrauta sūtra - Ānartīya; Govinda (Disciple of Madhusūdana); Hillebrandt, Alfred, 1853-1927 (Bibliotheca Indica ;, 1981)
Aphoristic work, with commentaries, on Vedic sacrifices.